Produção de gerânio (Pelargonium graveolens) e óleo essencial em sistemas de cultivos e adubações com plantas oriundas de cultura in vitro - Rabelo, Paulo Gonçalves (2014)
Geranium (Pelargonium graveolens L.) is widely used for extraction of essential oil. Essential oils are produced by secondary metabolism of plant and its production is influenced by biotic and environmental factors. In this context, the aim of this study was to investigate the influence of crop system (greenhouse and open field) and the type of fertilizer (organic and chemical) on the biomass production, productivity and chemical composition of the essential oil of geranium. The study was conducted at Farm of Glória, belonged to the Federal University of Uberlândia, Uberlândia, Minas Gerais state, in the period of May to October 2012. The plants with the greatest heights, as well as those which had the highest fresh and dry biomass were observed in the greenhouse using organic fertilizer. Oil production was higher in the field when compared to the greenhouse. The essential oil produced by the plant presented 18 chemical components, and geraniol was the most abundant. Thus, the results obtained showed that the crop system associated with the type of fertilization influence the development, production and quality of the essential oil of geranium.